VARIABILITY OF CHLOROPHYLL-A CONCENTRATION AND ITS RELATION TO THE CATCHES OF SMALL PELAGIC FISH IN THE KARIMATA STRAIT WATERS - Zumri Arza, Sy
Karimata Strait is known to have high prolificacy based on the abundance of chlorophyll-a and fisheries potential. Karimata Strait is a part of WPP 711 ranked third in Indonesia for fish productivity (after WPP 718-Arafura Sea and WPP 572-Hindia Ocean in west of Sumatra and Sunda Strait). This research aims to study the variability of chlorophyll-a concentration, utilizing satellite imagery Aqua MODIS spatially and temporally, to review its relation to the catches of small pelagic fish. This study uses Aqua MODIS level-3 chlorophyll-a and SST satellite images data with an addition of fish catches data from Pemangkat and Tj. Pandan national fishing port. The interval of the imageries span from 2008 – 2018. The study area is divided into 8 observation points throughout Karimata Strait. The result of this research shows that temporally, chlorophyll-a in Karimata Strait is higher in western monsoon and eastern monsoon (highest in July) whereas SST tends to be higher in the transitional season (highest in May). The influence of IOD and ENSO to the distribution of chlorophyll-a is not significant with a low average correlation coefficient (r<0.1). The influence of Western North Pacific Monsoon and Australian Monsoon is moderately strong in offshore waters with the correlation of -0.52 and 0.61 respectively. The correlation between chlorophyll-a and SST is found to be -0.14 (very low). The rainfall affects the distribution of chlorophyll-a with a moderately strong correlation in observation point 4 (r=-0.47) and 6 (r=0.44) which is near the river mouth. Spatially, the east coast of Sumatra and west coast of Borneo have high chlorophyll-a because of seasonal influence with an adequately high chlorophyll-a monthly average climatology in December–February and June–August. The correlation of chlorophyll-a to the CPUE of fish in Pemangkat fishing port shows a high value in the transitional season 1 (r=0.39) for Decapterus spp also in the transitional season 2 (r=0.42) for Selaroides spp. Whereas in Tj. Pandan fishing port, the correlation of chlorophyll-a with the CPUE of Sardinella gibbosa and Selaroides spp tends to be high in the eastern monsoon with a correlation of -0.35 and -0.16. The correlation of SST with the CPUE of those three fish species tend to be high in the western monsoon. The correlation of SST with the CPUE of Decapterus spp and Selaroides spp in Pemangkat fishing port is 0.31 and 0.36 while the correlation of SST with the CPUE of Sardinella gibbosa and Selaroides spp in Tj. Pandan fishing port is -0.34 and -0.42.